LEGAL STUDY ON THE EXTENSION OF THE TERM OF OFFICE OF VILLAGE HEAD AND ITS IMPLICATIONS ON THE STABILITY OF VILLAGE GOVERNMENT - Henny Simarmata; Abdul Rahman Maulana Siregar; Fauzan , Fauzan (International Journal of Synergy in Law, Criminal, and Justice, 2025)
The extension of the village head's term of office has become an interesting issue in the dynamics of legal politics in Indonesia, considering its crucial role in the stability of village government. The change in term of office from 6 to 9 years has raised a debate between government effectiveness and democratic principles. Supporters argue that this extension increases the stability and sustainability of village development, while opponents consider it to be risky to strengthen patronage politics and hinder leadership regeneration. The main focus of this study is to analyze the legal basis underlying the extension of the village head's term of office and how this policy affects the stability of village government. The research method used is the normative legal method with a statutory and conceptual approach, and is supported by an analysis of various relevant regulations. Research shows that the extension of the village head's term of office has a legal basis in the changes to village government regulations that aim to improve leadership effectiveness and the sustainability of village development programs. However, this policy also raises various challenges, especially related to aspects of democracy, accountability, and control over the implementation of village government. Without a strict monitoring mechanism, extension of office can increase the risk of abuse of power and reduce community participation in the village government process.